Controversial aspects of the modern national doctrine of property law - S. O. Serbenyuk (Law and Safety)
The article examines the basic controversial aspects of modern property law in the context of an overview of the Ukrainian legislation and highlights the main ideas of national civil law scholars on certain controversial issues. They consist in identifying the debatable components in the spectrum of research in the field of national property law, assessing further effective areas of scientific research and reviewing the main provisions of civil law on property rights. The author presents the main scientific views and contradictions, as well as the legislator’s views on the concept and features of real rights; reviews the points of view of understanding the grounds for the emergence of real rights and their generalisation and systematisation in the context of current legislation; demonstrates the problems of classification of objects of real rights; considers the problem of classification of real rights; reviews the content of basic legal categories related to the term “protection of real rights” and briefly highlights the approaches to classification of methods and forms of protection of real rights.